2016
DOI: 10.1021/acschembio.5b01063
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Proteomics Reveals Ferrochelatase as a Common Off-target of Kinase Inhibitors

Abstract: Many protein kinases are valid drug targets in oncology because they are key components of signal transduction pathways. The number of clinical kinase inhibitors is on the rise, but these molecules often exhibit polypharmacology, potentially eliciting desired and toxic effects. Therefore, a comprehensive assessment of a compound's target space is desirable for a better understanding of its biological effects. The enzyme ferrochelatase (FECH) catalyzes the conversion of protoporphyrin IX into heme and was recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(99 citation statements)
references
References 46 publications
6
92
0
1
Order By: Relevance
“…Whereas CIT was assigned a high SAINT score and displayed a high fold change, its large size of 230 kDa and the relatively few peptides identified for this protein (Table S1) suggest that CIT is likely not a strong niraparib interactor. The mitochondrial enzyme FECH was recently found to bind to many small molecule kinase inhibitors (Klaeger et al, 2016; Savitski et al, 2014) and was observed in our data with niraparib, but, similarly to CIT, showed only low spectral counts (Table S1). The most prominent unique niraparib candidate identified was DCK, which is responsible for the monophosphorylation of deoxycytidine, deoxyadenosine, and deoxyguanosine in the rate-limiting step of the nucleotide salvage pathway.…”
Section: Resultssupporting
confidence: 73%
“…Whereas CIT was assigned a high SAINT score and displayed a high fold change, its large size of 230 kDa and the relatively few peptides identified for this protein (Table S1) suggest that CIT is likely not a strong niraparib interactor. The mitochondrial enzyme FECH was recently found to bind to many small molecule kinase inhibitors (Klaeger et al, 2016; Savitski et al, 2014) and was observed in our data with niraparib, but, similarly to CIT, showed only low spectral counts (Table S1). The most prominent unique niraparib candidate identified was DCK, which is responsible for the monophosphorylation of deoxycytidine, deoxyadenosine, and deoxyguanosine in the rate-limiting step of the nucleotide salvage pathway.…”
Section: Resultssupporting
confidence: 73%
“…The increasing power and adoption of ABPP is revealing the potential for off-target pharmacology with current drugs and chemical tools. For example, a recent report highlights a chemical proteomics approach that revealed the enzyme ferrochelatase (FECH) as a surprisingly common off-target of kinase inhibitors; notably, 29 of the 226 clinical kinase inhibitors tested, including approved drugs vemurafenib and neratinib, bind to the protoporphyrin pocket of FECH at low- or sub-micromolar concentrations (Klaeger et al., 2016); this is known as “pharmacophore crossing” (see Box 1). …”
Section: Main Textmentioning
confidence: 99%
“…Cell lines were kindly provided by the NCI‐Frederick Cancer DCTD Tumor/Cell line repository, were not found in the database of commonly misidentified cell lines (ICLAC) and were tested negatively for mycoplasm contamination. Cell lysis and Bradford assay were performed as described previously . Kinase affinity matrices were prepared in house as published elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…Cell lysis and Bradford assay were performed as described previously . Kinase affinity matrices were prepared in house as published elsewhere …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation